The Image and Likeness of God in Bernard of Clairvaux's Free Choice and Grace: Reflections Both Philosophical and Theological - Casey, Michael (Cistercian studies quarterly, 2006)
The article reviews the book "The Image and Likeness of God in Bernard of Clairvaux's Free Choice and Grace: Reflections Both Philosophical and Theological," by Luke Anderson.